The Effectiveness of Modern Acoustic Music as Distraction Technique for Reducing Menstrual Pain - Dyah Nuril Hasanah; Eny Sendra; Lumastari Ajeng Wijayanti (Journal of Ners and Midwifery, 2024)
Menstrual discomfort is characterized by lower abdominal cramps with varying intensity ranging from mild to severe. The root cause of menstrual discomfort lies in the increased or imbalanced production of endometrial prostaglandins during menstruation. Menstrual discomfort has negative impacts on daily life by disrupting activities, reducing focus and motivation for learning, and causing significant financial losses due to the high costs of medication and medical treatments. The aim of this study was to determine the effectiveness of using acoustic music as a distraction method to reduce menstrual pain. Research sample of 38 respondents was selected using simple random sampling from a total population of 256 students. This study employed a pre-experimental design with a one-group pretest-posttest procedure. Research instrument consist menstrual data, general questionnaire sheets, Numeric Rating Scale (NRS) sheets, standard operating procedures (SOPs), smartphones, earphones, and modern audio music. The data analysis indicated that the use of modern acoustic music as distraction technique was effective to reduce menstrual pain among female students at SMAN 4 Kota Kediri